Designing the BPP Air Sijorman Website as a Media for Agricultural Extension and Information Dissemination - Gusti Setiavani; Elrisa Ramadhani; Mulya Suderajat (Altifani Journal: International Journal of Community Engagement, 2024)
Information Technology and Communication played a important role in the execution of tasks by the Agricultural Extension and Research Agency (BPP). BPP Air Sijorman, located in Asahan Regency, was previously without a website. A community service initiative was undertaken to design a website for BPP Air Sijorman, serving as a platform for agricultural extension and the dissemination of information. The process commenced with socialization and the identification of system needs, followed by website design, implementation, and user training.  The website was conceptualized using CorelDRAW and physically designed by aligning the graphics with the source code on the website. The implemented system resulted in the creation of the BPP Air Sijorman website, which was accessible via both desktop and mobile devices at http://bpp-airjoman.website/beranda.html. The website offered information on farming guidelines, the latest news, agricultural policies, and the BPP profile, accessible through various menus. The response from both BPP and farmers to the BPP Air Sijorman website was highly positive. On average, participants in the training sessions demonstrated the ability to operationalize and effectively use the website. Participants also expressed satisfaction with the website's visually appealing design, user-friendly interface, informative content, simplicity, and easily understandable instructions. This positive feedback underscored the effectiveness of the implemented website, making it a valuable tool for agricultural extension and information dissemination.